Mitteilungen aus dem Brenner-Archiv Nr. 38-39/2019/2020 - Unterkircher, Anton (Mitteilungen aus dem Brenner-Archiv, 2019)
The journal "Mitteilungen aus dem Brenner-Archiv" has been published regularly since the early 1980s (No. 1/1982). It provides information on the activities of the research institute Brenner-Archiv: on new estates, research projects and on current publications. In addition, scolarly contributions from international authors are included, whose research areas range from literary studies to philosophy and (cultural) history. The papers mainly refer to topics related to the "Brenner", the "Brenner"-circle or the more than 300 estates of the institute (especially from "Brenner" employees and Tyrolean authors of the 19th and 20th Century).